Voice-over as a didactic resource in foreign language education: The VOCAL Project - Talaván, Noa; Tinedo-Rodríguez, Antonio-Jesús (Meta, 2024)
The VOCAL (VOiCe-over and lAnguage Learning) Innovation Project is aimed at assessing the potential didactic benefits of using the audiovisual translation (AVT) mode of voice-over as a resource in foreign language (FL) education. The experimental design consisted of a didactic intervention in which students had to complete six voice-over-based lesson plans in which they had to create their own voice-over versions of six pre-selected short video extracts. The lesson plans were designed bearing in mind the importance of developing integrated skills and linguistic mediation. The nature of the study is mixed, since quantitative and qualitative variables have been considered to triangulate the perception of the participants with the data obtained from proficiency tests of integrated skills. The main findings of this study point towards a series of benefits of using didactic voice-over and the results seem to converge towards an improvement of production skills. In addition, development of oral reception was also observed and, subsidiarily, there was also an improvement in digital skills and linguistic mediation. The conclusions are consistent with the very nature of performing voice-over and call for further research in the area.